REKONSTRUKSI MODEL MANAJEMEN RAHMAH BERBASIS KEPERCAYAAN DALAM MENGATASI KONFLIK KOMUNIKASI KEPALA SEKOLAH DAN GURU (STUDI KASUS DI SD NEGERI 029/XI CEMPAKA - Ari Novera; Inestia Pariza; Wisnarni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to reconstruct a rahmah-based management model grounded in trust to address communication conflicts between the principal and teachers. Communication conflicts in school organizations often arise due to differences in perceptions, lack of information transparency, and weak trust relationships between leaders and organizational members. Therefore, a management approach is needed that not only emphasizes administrative aspects but also incorporates humanitarian and spiritual values in educational leadership. This research employed a qualitative approach with a case study design conducted at SD Negeri 029/XI Cempaka. The research subjects consisted of the principal and several teachers selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, while data analysis used an interactive analysis model including data reduction, data display, and conclusion drawing. The results show that communication conflicts between the principal and teachers occur in the form of misunderstandings in information delivery, differences in perceptions regarding school policies, and a lack of two-way communication. The factors causing these conflicts include differences in communication styles, limited time for organizational communication, and low levels of trust in working relationships. This study finds that the implementation of rahmah-based management grounded in trust, through open communication, empathetic leadership, transparency in decision-making, and appreciation of teachers’ roles, can be an effective strategy to overcome communication conflicts in schools. This model is expected to create harmonious, collaborative, and productive working relationships between principals and teachers in supporting the achievement of educational goals.